Heterogeneity of microvascular pericytes for smooth muscle type alpha- actin (The Rockefeller University Press, 1991)
Microvascular pericytes are believed to be involved in various functions such as regulation of capillary blood flow and endothelial proliferation. Since pericytes represent a morphologically heterogeneous cell population ranging from circular smooth musclelike to elongated fibroblast-like morphology it is possible that regulation of blood flow (via contractility) and control of endothelial proliferation (as well as other metabolic functions) may be accomplished by different subsets of pericytes. In the present study we provide evidence for heterogeneity of pericytes at the molecular level by using two novel technical approaches. These are (a) immunostaining of whole mounts of the microvascular beds of the rat mesentery and bovine retina and (b) immunoblotting studies of microdissected retinal microvessels. We show that pericytes of true capillaries (midcapillaries) apparently lack the smooth muscle isoform of alpha- actin whereas transitional pericytes of pre- and postcapillary microvascular segments do express this isoform. Thus, regulation of capillary blood flow may be accomplished by the smooth muscle-related pre- and postcapillary pericytes whereas the nonmuscle pericytes of true capillaries may play a role in other functions.